2009
DOI: 10.1103/physreve.80.066303
|View full text |Cite
|
Sign up to set email alerts
|

Helical magnetorotational instability in a Taylor-Couette flow with strongly reduced Ekman pumping

Abstract: The magnetorotational instability (MRI) is thought to play a key role in the formation of stars and black holes by sustaining the turbulence in hydrodynamically stable Keplerian accretion disks. In previous experiments the MRI was observed in a liquid metal Taylor-Couette flow at moderate Reynolds numbers by applying a helical magnetic field. The observation of this helical MRI (HMRI) was interfered with a significant Ekman pumping driven by solid end caps that confined the instability only to a part of the Ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 65 publications
6
82
0
Order By: Relevance
“…In [45][46][47] it was shown that the HMRI traveling wave appears only in the predicted finite window of the magnetic field intensity, with a frequency of the traveling wave that was in rather good accordance with numerical simulations. Some disturbing effects of this early version (PROMISE 1), connected with the recirculating radial jet at midheight of the cylinder, were overcome in the follow-up PROMISE 2 experiment by splitting the axial end caps to suppress the Ekman pumping [48,49]. By comparing experimental and numerical (based on [50]) results for a wide variety of parameter dependencies, it was possible to identify the observed instability as an absolute one, distinguishing it clearly from a noise triggered convective instability as speculated on in [51].…”
Section: Introductionmentioning
confidence: 99%
“…In [45][46][47] it was shown that the HMRI traveling wave appears only in the predicted finite window of the magnetic field intensity, with a frequency of the traveling wave that was in rather good accordance with numerical simulations. Some disturbing effects of this early version (PROMISE 1), connected with the recirculating radial jet at midheight of the cylinder, were overcome in the follow-up PROMISE 2 experiment by splitting the axial end caps to suppress the Ekman pumping [48,49]. By comparing experimental and numerical (based on [50]) results for a wide variety of parameter dependencies, it was possible to identify the observed instability as an absolute one, distinguishing it clearly from a noise triggered convective instability as speculated on in [51].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the LLL, together with a variety of further predicted parameter dependencies, was experimentally confirmed in the PROMISE facility, a Taylor-Couette cell working with a low Pm liquid metal (Stefani et al , 2007(Stefani et al , 2009. Present exper-imental work at the same device (Seilmayer et al 2014) aims at the characterization of the azimuthal MRI (AMRI), a non-axisymmetric "relative" of the axisymmetric HMRI, which dominates at large ratios of B φ to B z ).…”
Section: Introductionmentioning
confidence: 99%
“…The HMRI is an inductionless instability since it survives at the vanishing magnetic Reynolds number limit, in contrast to the standard MRI. It exhibits a form of traveling waves (Liu et al, 2007) which have been subsequently reproduced in the PROMISE experiments (Stefani et al, 2006;Stefani et al, 2009). Once again, the importance of axial boundary conditions was demonstrated: in the original device with significant Ekman circulation the traveling waves were disrupted by returning radial flow slightly above the mid height, while the traveling waves propagate smoothly throughout the flow when Ekman circulation is reduced by modified end caps, see Fig.2.…”
Section: Magnetohydrodynamic (Mhd) Experimentsmentioning
confidence: 81%